2022
DOI: 10.1155/2022/3132016
|View full text |Cite|
|
Sign up to set email alerts
|

Intervention Effect of Group Counseling Based on Positive Psychology on Psychological Crisis of College Student

Abstract: Objective. To analyze the intervention effect of group counseling based on positive psychology on psychological crisis of college student. Method. SCL-90 mental health screening was performed on second-year students in a college by cluster stratification. Among the detected students, 210 were included into the group after brief interview and randomly assigned to the experimental group and the control group. The control group was given conventional intervention measures, and the experimental group was given gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…This study also found that optimism was positively correlated with self-management ability, most likely because the more positive AF patients' attitudes toward the disease and life after RFCA, the more likely they are to use positive coping methods to manage the disease, resulting in stronger self-management ability [35]. In conclusion, when caring for women with AF following RFCA, healthcare professionals should focus on positive psychological capital and help patients develop positive psychological qualities, which can be guided by positive psychology theory, and improve patients' self-efficacy or confidence, resilience, hope, and optimism through group psychological guidance [36], PERMA model intervention [37], and role model education [38], etc. To address patients' postoperative psychological issues while cultivating their positive and healthy psychological qualities, thereby promoting patients' self-management ability and early disease recovery.…”
Section: Psychological Capital Is a Key Predictor Of Women Patients' ...mentioning
confidence: 99%
“…This study also found that optimism was positively correlated with self-management ability, most likely because the more positive AF patients' attitudes toward the disease and life after RFCA, the more likely they are to use positive coping methods to manage the disease, resulting in stronger self-management ability [35]. In conclusion, when caring for women with AF following RFCA, healthcare professionals should focus on positive psychological capital and help patients develop positive psychological qualities, which can be guided by positive psychology theory, and improve patients' self-efficacy or confidence, resilience, hope, and optimism through group psychological guidance [36], PERMA model intervention [37], and role model education [38], etc. To address patients' postoperative psychological issues while cultivating their positive and healthy psychological qualities, thereby promoting patients' self-management ability and early disease recovery.…”
Section: Psychological Capital Is a Key Predictor Of Women Patients' ...mentioning
confidence: 99%
“…As positive psychology has been applied in the field of education, now teachers have paid more attention to students' positive emotions in the class, especially the bilingual teachers who need to interact with students more often [1][2][3][4][5][6]. Studies have shown that students' willingness to engage in bilingual communication is significantly influenced by their positive emotions in the bilingual class [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%